1998
DOI: 10.1111/j.1469-7793.1998.743bj.x
|View full text |Cite
|
Sign up to set email alerts
|

Na+‐activated K+ channels in small dorsal root ganglion neurones of rat

Abstract: Whole‐cell Na+‐activated K+ (KNa) channel currents and single KNa channels were studied with the patch‐clamp method in small (20‐25 μm) dorsal root ganglion (DRG) neurones in slices of rat dorsal root ganglia. The whole‐cell KNa channel current was identified as an additional K+‐selective leakage current which appeared after cell perfusion with internal solutions containing different [Na+]. The concentration for half‐maximal activation of KNa channel current was 39 mM and the Hill coefficient was 3.5. At [Na+]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
51
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 29 publications
3
51
0
Order By: Relevance
“…• K Na Channels Are Modulated by NAD ϩ nohistochemical data and is similar to what has been reported earlier (Bischoff et al, 1998;Gao et al, 2008). The K Na channel EC 50 s for Na ϩ was determined to be 53 mM (n ϭ 6) and 55 mM (n ϭ 6) in small neurons (Fig.…”
Section: K Na Channels In Drg Neuronssupporting
confidence: 70%
See 3 more Smart Citations
“…• K Na Channels Are Modulated by NAD ϩ nohistochemical data and is similar to what has been reported earlier (Bischoff et al, 1998;Gao et al, 2008). The K Na channel EC 50 s for Na ϩ was determined to be 53 mM (n ϭ 6) and 55 mM (n ϭ 6) in small neurons (Fig.…”
Section: K Na Channels In Drg Neuronssupporting
confidence: 70%
“…Previous work has documented that K Na channels can be recorded in small-and medium-sized DRG neurons (Bischoff et al, 1998;Gao et al, 2008), and we have now demonstrated that K Na channels are also present in large, proprioceptive DRG neurons. The Na ϩ -doseresponse relationship for K Na channels for both small and large DRG neurons was determined to be similar.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…In addition, the calcium current most likely activates a counterbalancing calcium-activated potassium current during the action potential shoulder. In contrast, Na entry through TTX-R sodium channels probably does not activate a potassium current; although Na-activated potassium currents are known to exist in small DRG neurons, they do not appear to be activated during single action potentials (Bischoff et al, 1998).…”
Section: Discussionmentioning
confidence: 99%